(untitled) (International Journal of Environmental Sciences, 2025)
The surge of refugees into India has significantly increased in recent years, presenting challenges and opportunities for the protection of their rights within the country's legal framework. Even though the Constitution of India does not specifically confer the specific right to refugees, but several provisions protect their fundamental rights. The Judiciary has elucidated the core essence of Article 21 which expansively includes the refugees as well. The Indian Constitution recognizes the concept of non-refoulement, which interdict the deportation of refugees to territories where there is a potential risk of their individual freedom and liberty. However, there exists no specific legal framework that comprehensively addresses the rights and status of refugees in India. Consequently, the judiciary has played a pivotal role in interpreting and expanding the constitutional provisions to afford adequate protection to this vulnerable population. The Indian judiciary's approach towards protecting the rights of refugees, reflects the nation's commitment to upholding the principles of justice and humanitarian values.